2019
DOI: 10.1038/s41598-019-51235-4
|View full text |Cite
|
Sign up to set email alerts
|

Wire-like Pt on mesoporous Ti0.7W0.3O2 Nanomaterial with Compelling Electro-Activity for Effective Alcohol Electro-Oxidation

Abstract: Finding out robust active and sustainable catalyst towards alcohol electro-oxidation reaction is major challenges for large-scale commercialization of direct alcohol fuel cells. Herein, a robust Pt nanowires (NWs)/Ti0.7W0.3O2 electrocatalyst, as the coherency of using non-carbon catalyst support and controlling the morphology and structure of the Pt nanocatalyst, was fabricated via an effortless chemical reduction reaction approach at room temperature without using surfactant/stabilizers or template to assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The width was about 4 nm, and the measured lattice fringe spacing was about 0.228 nm, corresponding to the (111) crystal plane of the face-centered cubic crystal structure of Pt, which indicated that Pt was mainly growing along the (111) crystal plane . The growth mechanism of Pt nanowires on GO was similar to that reported by other groups. ,,, Briefly, chloroplatinic acid was first reduced with formic acid to form platinum nuclei. The platinum nuclei were then deposited onto the monolayered GO due to the abundant oxygenated groups of GO.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The width was about 4 nm, and the measured lattice fringe spacing was about 0.228 nm, corresponding to the (111) crystal plane of the face-centered cubic crystal structure of Pt, which indicated that Pt was mainly growing along the (111) crystal plane . The growth mechanism of Pt nanowires on GO was similar to that reported by other groups. ,,, Briefly, chloroplatinic acid was first reduced with formic acid to form platinum nuclei. The platinum nuclei were then deposited onto the monolayered GO due to the abundant oxygenated groups of GO.…”
Section: Resultssupporting
confidence: 77%
“…In most reports on the synthesis of platinum-based nanomaterials, surfactants were usually added to control the morphology of platinum . However, surfactants would tend to adsorb on the electrocatalytically active sites of platinum, which would result in the reduction of the electrocatalytic activity of platinum . In order to avoid this problem, surfactant-free methods have been developed. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations